Construction and testing of sMDT tubes at the University of Michigan for the ATLAS Muon Spectrometer upgrade. (1st October 2022) - Wei, C.; Chen, A.; Amidei, D.; Anderson, N.; Carpenter, E.; Cooperrider, L.; Dai, T.; Diehl, E.; Ferretti, C.; Li, J.; Lugato, P.; Minnella, J.; et al.
Abstract: This paper reports on the design and construction of infrastructure and test stations for small-diameter monitored drift tube (sMDT) assembly and testing at the University of Michigan (UM) to prepare for the ATLAS Muon Spectrometer upgrade for the high-luminosity program of the Large Hadron Collider. Procedures of the tube assembly and quality assurance and control (QA/QC) tests are described in detail. More than 99% of the tubes meet the tube QA/QC specifications based on 2100 tubes built at UM. The UM test stations are also used for QA/QC testing on the tubes constructed at Michigan State University. These tubes are being used to construct the sMDT chambers which will replace the current MDT chambers of the barrel inner station of the Muon Spectrometer.